A novel Al₀.₃₃Ga₀.₆₇As/In₀.₁₅Ga₀.₈₅As/GaAs quantum well Hall device grown on (111) GaAs - Sghaier, H.; Bouzaiene, L.; Sfaxi, L.; Maaref, H. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
In this study, we look at the advantages of (111) GaAs substrate over (001) one, when used to grow Hall devices by MBE. In top of that, we explore the consequence of a modified design of modulation doping pseudomorphic AlGaAs/InGaAs/GaAs, and we suggest a new quantum well structure for a Hall device grown on (111) GaAs substrate, with the objective of improving its performances. From self-consistent calculations, we find that the electron concentration ns in the interface region is enhanced. This implies that one can have a wider spacer layer and still have the same ns with the result that the mobility is improved. This result should be valuable for many types of devices. We specifically consider Hall sensors, where it is desirable to have a low electron concentration and high mobility.